A sociotechnical systems approach to enhance safety climate in the trucking industry: Development of a methodology. (January 2018) - Murphy, Lauren A.; Robertson, Michelle M.; Huang, Yueng-hsiang; Jeffries, Susan; Dainoff, Marvin J.
Abstract: The systems approach is increasingly used as a framework within which to examine safety climate. Utilizing a macroergonomics approach to design work systems can help identify aspects of human-technology-organization interfaces that impact workers' perceptions of safety, both positively and negatively. Such an approach also supplements traditional uses of safety climate as a leading indicator of safety and helps expand research toward an approach that can determine problems impacting safety. The purpose of this study was to develop a methodology that extends safety climate beyond just an overall score by using the framework of macroergonomics to examine the entire system in a more comprehensive manner. The proposed methodology can be used as a way to identify gaps in the specific work system, and this information can be used to design interventions to change the safety climate, and ultimately the culture, of an organization in order to reduce negative safety outcomes. Highlights: Often safety climate measures do not identify underlying causes of poor safety. The limited items in climate measures usually address global safety concerns. Macroergonomics examines a work system in a more comprehensive manner. The proposed methodology can be used to design safety interventions.